STUDY TO ASSESS BREAST FEEDING SELF-EFFICACY AMONG POSTNATAL MOTHERS AT JAI PRAKASH HOSPITAL, BHOPAL M.P. (CAHIERS MAGELLANES-NS, 2024)
Background: Breastfeeding is vital to a child’s lifelong health, and reduces costs for health facilities, families, and governments. Breastfeeding within the first hour of birth protects newborn babies from infections and saves lives. Infants are at greater risk of death due to diarrhoea and other infections when they are only partially breastfed or not breastfed at all. Breastfeeding also improves IQ, school readiness and attendance, and is associated with higher income in adult life. It also reduces the risk of breast cancer in the mother. “Breastfeeding saves lives. Its benefits help keep babies healthy in their first days and last well into adulthood,” Materials and Methods: A quantitative research approach and non-experimental descriptive exploratory design was adopted. The study was conducted on 60 postnatal mothers admitted at Hamidiya General Hospital using a convenient sampling technique. Data was collected from a structured knowledge questionnaire and obtained data was analyse by descriptive and inferential statistics. Results: Regarding breastfeeding self-efficacy among post-natal mothers, 23.3% of mothers had low confidence, 33.3% of mothers had moderate confidence, 43.3% of mothers had high confidence. Conclusion: The findings revealed that the improve the breast feeding self-efficacy of postnatal mother.